Dearomatization of 3-cyanoindoles by (3 + 2) cycloaddition: from batch to flow chemistry. Issue 18 (29th April 2020) - Manneveau, Maxime; Tanii, Saori; Gens, Fanny; Legros, Julien; Chataigner, Isabelle
Abstract : (3 + 2) Dearomatizing cycloaddition of 3-cyanoindoles occurs in smooth conditions with a non-stabilized azomethine ylide, to yield tricyclic indolines in only 1 min under microflow conditions using 3 equiv of the dipole precursor vs. 6 equiv. in a batch reactor. Abstract : 1, 3-Dipolar dearomatizing cycloadditions between a non-stabilized azomethine ylide and 3-cyanoindoles or benzofuran afford the corresponding 3D-heterocycles bearing a quaternary carbon centre at the ring junction. While 6 equivalents of ylide precursor 1 are required for full conversion in a classical flask, working under flow conditions limits the excess (3 equiv., t R = 1 min) and leads to a cleaner process, affording cycloadducts that are easier to isolate.